Engineering Dynamics and Vibrations - Jia, Junbo; Paik, Jeom Kee; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Engineering dynamics and vibrations has become an essential topic for ensuring structural integrity and operational functionality in different engineering areas. However, practical problems regarding dynamics and vibrations are in many cases handled without success despite large expenditures. This book covers a wide range of topics from thebasics to advances in dynamics and vibrations; from relevant engineering challenges to the solutions; from engineering failures due to inappropriate accounting of dynamics to mitigation measures and utilization of dynamics. It lays emphasis on engineering applications utilizing state-of-the-art information.
Table of contents -- Introduction to Dynamics, Vibrations and Impacts -- Junbo Jia -- Nonlinear Structural Responses Associated with Hydrocarbon Explosions -- Jeom Kee Paik -- Stochastic Dynamic Analysis of Marine Structures -- Bernt J. Leira -- Mitigation of Stresses and Vibrations in Deep-water Steel Riser Design by Introducing a Lazy Wave Geometry -- Felisita, Airindy, Gudmestad, Ove T., and Karunakaran, Daniel -- Wind Induced Dynamic Response Calculations -- Einar N. Strmmen -- Neo-Deterministic Scenario-Earthquake Accelerograms and Spectra: a NDSHA Approach to Seismic Analysis -- Paolo Rugarli, Claudio Amadio, Antonella Peresan, Marco Fasan, Franco Vaccari, Andrea Magrin, Fabio Romanelli and Giuliano F. Panza -- Ground Motion Prediction Equations for Energy-Based Demand Parameters: Regional Application to Northwestern Turkey -- Ali SARIA and Lance MANUEL -- Nonlinear Seismic Analysis of Framed Structures -- Stelios Antoniou, and Rui Pinho -- Seismic Mitigation of Single Pylon Cable-Stayed Bridge -- Qiang Han, Jianian Wen, and Xiuli Du -- Principles of Noise Control -- James K. Thompson.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Civil / Earthquake; TECHNOLOGY & ENGINEERING / Structural; Sloshing dynamics; Structural dynamics; Wave propagation dynamics; Dynamics; Vibration; Electronic books